Corrosion-fatigue crack growth behaviour of wire arc additively manufactured ER100S-1 steel specimens - Ermakova, Anna; Ganguly, Supriyo; Razavi, Javad; Berto, Filippo; Mehmanparast, Ali (Elsevier, 2022)
The wire arc additive manufacturing (WAAM) technology is a promising fabrication technique which has been proven to have many advantages for producing large structures; however, the fatigue and corrosion-fatigue performance of WAAM steel components for application in the marine environments is still unexplored. In this study, the WAAM technique was employed to fabricate four specimens made of ER100S-1 steel, which were then tested under cyclic loading conditions in seawater to assess the corrosion-fatigue crack growth (CFCG) behaviour and hence suitability of this fabrication technology for offshore renewable energy applications. The test duration, cracking mechanisms and CFCG rate were investigated for each specimen and the material’s behaviour was investigated by considering the microstructural examinations. Furthermore, the obtained results were compared with the BS7910 standard recommended trends and experimental data available in the literature for conventionally built weldments made of different grades of steel which are commonly used for offshore applications.
Keywords: Corrosion-fatigue; WAAM; Additive manufacturing; Offshore structures; Structural Integrity